Supply Chain Management with APO Structures, Modelling Approaches and Implementation of mySAP SCM 4.1 - Dickersbach, Jörg Thomas (Springer Berlin Heidelberg : Imprint: Springer, 2006)
The Advanced Planner and Optimiser (APO) is the software from SAP dedicated to supply chain management. This book provides an overview about the supported SCM processes and explains how to implement APO in a company. It is written from a long years' experience in implementation projects and provides project managers and team members with the necessary know-how for a successful implementation project. The focus of the book is on introducing modelling approaches and explaining the structure and interdependencies of systems, modules and entities of APO based on the release mySAP SCM 4.1. Another concern is the integration with R/3, both technically and from a process point of view. Since APO projects differ significantly from other SAP projects, some key issues and common mistakes concerning project management are mentioned as well.